Effects of soccer match-play on muscle strength, physical performance, and perceptual responses in elite female players - Gereduz Agapito, L.; Brownstein, C. G.; Maffiuletti, N. A. (The Journal of Strength and Conditioning Research, 2025)
The purpose of this study was to investigate the impact of actual soccer match-play on muscle strength, physical performance, and perceptual responses in elite female players. Twelve Swiss elite players were tested before (pre), after (post) and 48 hours after a 90-minute soccer match for knee and hip muscle strength, vertical jump height, and sprint time. Perceptual responses were also evaluated up to 72 hours postmatch with a self-reported questionnaire. Muscle strength, jump, and sprint performance were impaired at post compared with pre (p < 0.001), but fully recovered at 48 hours. Percent strength losses were higher for knee flexors (~20%) compared with both hip adductors (~12%; p = 0.005) and abductors (8-12%; p < 0.001), and for knee extensors compared with hip abductors (p = 0.013). Regardless of muscle group, strength losses were higher on the dominant than on the nondominant side (p = 0.010). Most perceptual responses were altered after the match (p < 0.001) and some items such as motivation to train and readiness to play remained unrecovered at 72 hours (p < 0.01). Soccer match-play induced a significant decline of knee and hip muscle strength in elite female players that was more marked for knee flexors than for hip muscles. This was accompanied by performance impairments and by altered perceptual responses that still persisted 72 hours after the match. These findings offer implications for the optimization of postmatch recovery strategies in elite female soccer players.